PERBEDAAN ASERTIVITAS SISWA SMK NURUL AMALIYAH I DENGAN SMA NUR AZIZI DI TANJUNG MORAWA - tarigan, Mustika (JURNAL DIVERSITA, 2016)
This study aims to look at the differences assertivity vocational students between SMK Nurul Amaliyah I and SMA Nur Azizi in Tanjung Morawa. The subjects were students of SMK Nurul Amaliyah I with SMA Nur Azizi with male gender everything. Based on the translation of the existing chapter theoretical basis, the proposed hypothesis which says: there is a difference assertiveness vocational students SMK Nurul Amaliyah I and SMA Nur Azizi in Tanjung Morawa. This study used the analytical techniques Non-Parametric with sampling technique using Proportional Sample. Based on data analysis using non-parametric analysis using the Mann Whitney U, the result was no difference assertiveness vocational students of SMK Nurul Amaliyah I and SMA Nur Azizi in Tanjung Morawa. This result is known by looking at the value or coefficient differences Mann Whitney with a coefficient of 1016.000 to p (Asymp. Sig) = 0.000 < 0.010. With a mean rank at SMK Nurul Amaliyah I is 55.31 and the mean rank SMA at 118.32 Nur Azizi. Based on the analysis of data then the hypothesis is accepted.Key Words: Assertivity, SMK Nurul Amaliyah I, SMA Nur Azizi